Penokohan Perempuan sebagai Perlawanan Stereotipe Gender dalam Cerpen Siang Itu Panas Sekali Majalah Femina 1980 - Fitri, Sopia Wili; Sartika, Delita; Ningsih, Arum Gati (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2025)
Social constructions during Indonesia’s New Order era often shaped gender stereotypes that positioned women as self-sacrificing figures confined to domestic roles and economically dependent on men. This study aims to identify gender stereotypes attached to female characters and analyze their resistance to such stereotypes in the short story Siang Itu Panas Sekali, published in Femina magazine, edition of November 4, 1980, No. 196. Using a qualitative approach, this research applies content analysis with Mansour Fakih’s gender theory within a feminist literary framework. The findings reveal that the female character is portrayed as someone who sacrifices personal needs for the sake of her family. However, the story also illustrates resistance through the character’s involvement in social activities outside the home, financial independence, and assertiveness in confronting patriarchal control within personal relationships. The main character, Mira, is depicted as an educated, professionally active woman who is financially self-sufficient and firmly v oices her opinions to her husband. The conclusion of this study indicates that the short story not only reflects the prevailing gender norms of the 1980s but also functions as a narrative space of resistance, offering an alternative representation of women as autonomous and empowered individuals.